Suboptimal care for chronic pancreatitis patients revealed by moderate to low adherence to the United European Gastroenterology evidence‐based guidelines (HaPanEU): A Netherlands nationwide analysis. Issue 7 (1st August 2020) - de Rijk, Florence EM; Kempeneers, Marinus A; Bruno, Marco J; Besselink, Marc GH; van Goor, Harry; Boermeester, Marja A; van Geenen, Erwin JM; van Hooft, Jeanin E; van Santvoort, Hjalmar C; Verdonk, Robert C; ,
Abstract : Background and objective: The 2016, United European Gastroenterology evidence‐based guidelines for the diagnosis and therapy of chronic pancreatitis (HaPanEU) provided evidence‐based recommendations for the management of chronic pancreatitis and allowed for the objective evaluation of the quality of care in several domains of disease management through assessment of guideline adherence. Therefore, the aim of this study is to evaluate the current level and the variety of care for chronic pancreatitis patients in the Netherlands using the HaPanEU guidelines as a reference standard. The majority of these patients were diagnosed before the publication of these guidelines. Therefore, in most patients, the results of the present study with respect to those recommendations regarding the diagnostic process of chronic pancreatitis represent guideline correspondence and not adherence. Methods: A subgroup of patients from the Dutch nationwide chronic pancreatitis registry (CARE) was included in a retrospective cross‐sectional observational cohort study. A total of 39 recommendations concerning the non‐invasive management of chronic pancreatitis were appointed as quality indicators (QIs). Per patient, the number of relevant QIs was determined and guideline adherence was assessed. Data were analyzed to identify factors associated with guideline adherence. Results: Overall, 97 patients with chronic pancreatitis from 11 hospitals were included. Per patient, a mean number of 26 relevant QIs was applicable, with an average adherence rate of 53%. In 45% of the patients, guideline adherence was less than 50%. The majority of suboptimal managed QIs concerned the management of chronic pancreatitis complications. Guideline adherence was not associated with hospital type, sex, age or etiology of pancreatitis. Conclusion: In the Netherlands, adherence to the HaPanEU recommendations for the management of chronic pancreatitis is moderate to low for all non‐invasive domains, which may indicate suboptimal care for these patients. Closer guideline adherence could improve the level of care and the clinical outcomes of these patients. A nationwide approach to increase awareness of the key guideline recommendations among clinicians and patients is needed.